Penguatan Manajemen Kurikulum Terintegrasi Pada Madrasah di Lingkungan Pesantren - Mohammad Zaini (STAIFAS-Press, 2020)
Good integrated curriculum planning affects the implementation of curriculum in a good boarding school environment. The impact has a positive nuance for the development of curriculum management in Madrasah. The purpose of this research is to reveal: How to plan integrated curriculum on Madrasah in the pesantren environment in improving the quality of existing teachers. The study used a qualitative approach with multi-case design. Data validity collection and verification techniques. The results showed that (1) Integrated curriculum management in Madrasah in the boarding school needs to coordinate so that the curriculum is in accordance with the needs in three research locations, (2) The principal activities at the Madrasah And teachers can provide information to convey activity materials to students (3) The involvement of the principal in curriculum planning in the institution of boarding schools can exist if supported by local and national subjects. The conclusion of this study as follows (1) can improve teacher's professional and quality of education, (2) can improve the professionalism of teachers and students by the guidance on the new curriculum, (3) can meet the needs of society.